Evaluation of Curcumin-derived Carbon-dots' Inhibitory Activity as SARS-CoV-2 Antiviral Candidate Using Chemical Crosslinking - Taharuddin, Audrey Angelina Putri; Yamahoki, Nicholas; Stephanie, Rebecca; Agustiyanti, Dian Fitria; Wisnuwardhani, Popi Hadi; Angelina, Marissa; Rubiyana, Yana; Ningrum, Ratih Asmana; Wardiana, Andri; Desriani, Desriani; Hariyatun, Hariyatun; Iskandar, Ferry; Permatasari, Fitri Aulia; Giri-Rachman, Ernawati Arifin; Fibriani, Azzania (HAYATI Journal of Biosciences, 2026)
In our previous work, we demonstrated that curcumin-derived carbon dots (Cur-CDs) have potential as antivirals for COVID-19. However, the precise mechanism of action remains unclear. This study investigated the potential of Cur-CDs against SARS-CoV-2 by targeting the dimerization of the C-terminal domain of nucleocapsid protein (N-CTD) using chemical crosslinking. Recombinant SARS-CoV-2 N-CTD was expressed, purified, and subjected to chemical crosslinking. The dimerization inhibition ability of Cur-CDs was assessed with ligand concentrations ranging from 0 to 2,000 μg/mL. Successful inhibition —defined as a noticeable reduction in SARS-CoV-2 N-CTD dimer band intensity on SDS-PAGE—was observed when Cur-CDs were present at 8 to 16 times the protein concentration. We hypothesize that Cur-CDs bind to the dimerization residues, preventing non-covalent interactions between monomers and limiting dimer formation. Our findings suggest that Cur-CDs could be a promising antiviral strategy for SARS-CoV-2, especially targeting the dimerization of the nucleocapsid protein. Additionally, this study also highlights the use of chemical crosslinking as a valuable tool for interaction-based drug screening.